The Effect Of Debt To Equity Ratio And Total Asset Turnover To Return On Assets (Case Study At PT Charoen Pokphand Indonesia TBK For The Period Of 2003-2023 - Wulandari, Erdina; Yusnita, Rita Tri; Oktaviani, Nita Fauziah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this study are to find out how the effect of Debt To Equity Ratio (DER) and Total Asset Turnover (TATO) on Return On Assets (ROA) at PT Charoen Pokpand Indonesia Tbk. The research method used are quantitative. The data analyze tool used is multiple linear regression and coefficient of determination. Based on the result of the study, it is known that simultaneously between Debt To Equity Ratio (DER) and Total Asset Turnover (TATO) has a significant on Return On Assets (ROA). While partially between Debt To Equity Ratio (DER) has a significant effect on Return On Assets (ROA) and Total Assets Turnover (TATO) has a significant effect on Return On Assets (ROA).